Sistem Informasi Pencatatan Kesehatan Pegawai Dinas Kesehatan Provinsi Sumatera Selatan - Kurniawati, Hanni; Dhamayanti; Kholik, Abdul (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study aims to develop a web-based Employee Health Record Information System for the South Sumatra Provincial Health Office to enhance the efficiency of employee health data management. The developed system is designed to address issues associated with manual record-keeping, such as data loss, recording errors, and limited access to information. By applying the Waterfall method, the system is developed through the stages of requirements analysis, design, implementation, and testing. The results of this study indicate that the system facilitates employee health record management, improves data accuracy, and supports more effective decision-making for the Health Office. The implementation of this system also provides real-time information access for employees and medical personnel, thereby improving the quality of internal health services.